Internal in-frame translation generates Cas11b, which is important for effective interference in an archaeal CRISPR-Cas system - Sailer, A-L.; Brendel, J.; Chernev, A.; König, S.; Bischler, T.; Gräfenhan, T.; Urlaub, H.; Gophna, U.; Marchfelder, A. (Frontiers in Microbiology, 2025)
CRISPR-Cas is a sophisticated defence system used by bacteria and archaea to fend off invaders. CRISPR-Cas systems vary in their Cas protein composition and have therefore been divided into different classes and types. Type I systems of bacteria have been shown to contain the small protein Cas11 as part of the interference complex known as Cascade. Here we show for the first time that an archaeal CRISPR-Cas type I-B system also contains a homolog of Cas11. The Cas11b protein, encoded by the cas8b gene in Haloferax volcanii, represents the first known case of an internal in-frame translation of an archaeal protein. Translation initiation at an internal methionine of the cas8b open reading frame results in synthesis of Cas11b. Cas11b is required for an effective CRISPR-Cas interference reaction, and in its absence fewer Cascade complexes are formed. Comparison of transcriptomes from wild type and a Cas11b-less strain shows that the depletion of Cas11b also results in differential transcript abundance of many genes, presumably affecting their regulation. Taken together, Cas11b is important for the defence reaction of the type I-B CRISPR-Cas system and seems to play an additional cellular role.